Pregunta
upstudy study bank question image url

Find the general solution to the system corresponding to the following matrix. \[ A=\left[\begin{array}{llll|l}1 & 0 & 0 & 6 & 2 \\ 0 & 1 & 0 & 7 & 0 \\ 0 & 0 & 1 & 3 & 4 \\ 0 & 0 & 0 & 0 & 0\end{array}\right] \] \( \left[\begin{array}{l}x_{1} \\ x_{2} \\ x_{3} \\ x_{4}\end{array}\right]=\left[\begin{array}{lll}\text { Ex: 1-2x_3 } \\ \square & \\ \square\end{array}\right] \) Enter \( 1-2 x_{3} \) as: \( 1-2 \times 3 \)

Ask by Williams Weber. in the United States
Feb 22,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The general solution is: \[ \begin{cases} x₁ = 2 - 6t \\ x₂ = -7t \\ x₃ = 4 - 3t \\ x₄ = t \end{cases} \] where \( t \) is any real number.

Solución

We start with the augmented matrix:   [1 0 0 6 | 2]   [0 1 0 7 | 0]   [0 0 1 3 | 4]   [0 0 0 0 | 0] This corresponds to the system of equations:   1) x₁ + 6x₄ = 2   2) x₂ + 7x₄ = 0   3) x₃ + 3x₄ = 4 Since there is a free variable, let x₄ be free (we denote it by t ∈ ℝ). Solve each equation for its leading variable:   From (1): x₁ = 2 − 6t   From (2): x₂ = −7t   From (3): x₃ = 4 − 3t Thus, the general solution is:   x₁ = 2 − 6t   x₂ = -7t   x₃ = 4 − 3t   x₄ = t      with t ∈ ℝ In vector form, we can write:   [x₁, x₂, x₃, x₄]ᵀ = [2, 0, 4, 0]ᵀ + t[–6, –7, –3, 1]ᵀ This is the general solution to the system.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

The system described by the given matrix represents a series of linear equations derived from the reduced row echelon form. Let's rewrite the equations based on each row: 1. \( x_1 + 6x_4 = 2 \) 2. \( x_2 + 7x_4 = 0 \) 3. \( x_3 + 3x_4 = 4 \) Now, let's express the variables in terms of the free variable \( x_4 \). From the second equation: \[ x_2 = -7x_4 \] From the third equation: \[ x_3 = 4 - 3x_4 \] Substituting \( x_3 \) into the first equation gives: \[ x_1 = 1 - 2(4 - 3x_4) - 6x_4 \] \[ x_1 = 1 - 8 + 6x_4 - 6x_4 \] \[ x_1 = 1 - 8 \] So, we summarize the general solution as follows: \[ \begin{bmatrix} x_1 \\ x_2 \\ x_3 \\ x_4 \end{bmatrix} = \begin{bmatrix} -7 \\ -7x_4 \\ 4 - 3x_4 \\ x_4 \end{bmatrix} \] Thus, the complete expression in terms of \( x_4 \) becomes: \[ \begin{bmatrix} 1 - 2 \times (4 - 3x_4) \\ -7x_4 \\ 4 - 3x_4 \\ x_4 \end{bmatrix} \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad